2019
DOI: 10.1158/1055-9965.epi-18-0886
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Imaging Markers of Lung Function in a Smoking Population Distinguish COPD Subgroups with Differential Lung Cancer Risk

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a heterogeneous condition with respect to onset, progression, and response to therapy. Incorporating clinicaland imaging-based features to refine COPD phenotypes provides valuable information beyond that obtained from traditional clinical evaluations. We characterized the spectrum of COPD-related phenotypes in a sample of former and current smokers and evaluated how these subgroups differ with respect to sociodemographic characteristics, COPD-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Current clinical TKIs that target EGFR mutations include erlotinib, getfitnib, and afatinib ( Maemondo et al, 2010 ; Zhou et al, 2011 ; Sequist et al, 2013 ; Greathouse et al, 2018 ; Lusk et al, 2019b ). As mentioned previously, studies have shown that identifying the type of EGFR mutation a patient harbors in their NSCLC tumors may have significant clinical value in predicating response.…”
Section: Discussionmentioning
confidence: 99%
“…Current clinical TKIs that target EGFR mutations include erlotinib, getfitnib, and afatinib ( Maemondo et al, 2010 ; Zhou et al, 2011 ; Sequist et al, 2013 ; Greathouse et al, 2018 ; Lusk et al, 2019b ). As mentioned previously, studies have shown that identifying the type of EGFR mutation a patient harbors in their NSCLC tumors may have significant clinical value in predicating response.…”
Section: Discussionmentioning
confidence: 99%
“…14 Some studies, however, have proposed that the variance in lung function measures among smokers is not fully explained by the smoking intensity and the number of pack-years smoked did not affect the lung cancer rate in patients with COPD. 15 A study in 2017 16 said the annual frequency of lung cancer in never-smokers had more than doubled in the past 7 years, from 13% to 28%. This increase was due to an absolute increase in the number of never-smokers developing lung cancer, not simply a change in the ratio of never-smokers to current and former smokers.…”
Section: Why This Study Addsmentioning
confidence: 99%
“…[14] Some studies, however, have proposed that the variance in lung function measures among smokers is not fully explained by the smoking intensity and the number of pack-years smoked did not affect the lung cancer rate in patients with COPD. [15]…”
Section: Introductionmentioning
confidence: 99%